A canadian retrospective multicenter experience with selexipag in a heterogeneous group of pediatric pulmonary hypertension patients. (25th January 2023) - Youssef, D; Richards, S; Lague, S; Sheppard, C; Smith, J; Vorihes, E; Hosking, M; Pietrosanu, M; Bates, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The introduction of the oral prostanoid selexipag for treating severe adult pulmonary arterial hypertension (PH) has contributed to reduced rates of death and secondary complications in PAH. Pediatric physicians have extrapolated from the adult literature to utilize this medication to treat severe pediatric pulmonary hypertension. However, longitudinal, multicenter data on the therapeutic benefits of selexipag for pediatric patients is lacking. Materials and Methods: We performed a retrospective review describing the clinical outcomes of pediatric PH patients receiving selexipag for pulmonary hypertension (PH) therapy in addition to standard pulmonary vasodilator therapy across three North American pediatric PH centers between January 2005 and June 2021. Results: Across three Canadian centers, 24 patients (15 female) with a mean age at diagnosis of 5.4 (0.9) years were included. Of this cohort, 19 (79.2%) had group 1 PAH, 4 (16.7%) had group 3 PH, and 1 (4.2%) had group 4 PH. Genetic syndromes were noted in 7 (29.2%) patients. Dosing was targeted to achieve 20–30 mcg/kg/dose orally every 12 hours; the mean dosage after 12 months was 31.2 (10.3) mcg/kg/dose. Twelve months following selexipag initiation, a median increase of 71.5 m (p = 0.44) in six-minute walk test distance was observed together with median decreases of 0.2 cm (p = 0.17) in tricuspid annular plane systolic excursion, 3.5 mmHg (p = 0.95) in right ventricle systolic pressure, and 6.1 mmHg (p = 0.09) in mean pulmonary artery pressure. 2 patients (8.3%) died, 1 (4.2%) was referred for a heart transplant, and 1 (4.2%) received an atrial flow regulator. One patient (4.2%) required admission to a pediatric intensive care unit during their treatment course this was related to profound desaturation, six (25.0%) had gastrointestinal symptoms, and two (8.3%) had facial flushing. Conclusion: Selexipag appears to be a beneficial adjunctive therapy for selected pediatric PH patients and has a tolerable adverse effect profile aside from gastrointestinal disturbances. Further prospective studies of changes in hemodynamics and functional classification over a longer period and with a larger sample are needed.